(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The study was performed for investigating the dietary effect of different levels of mushroom (Agaricus bisporus) powder on the performance of broiler. Four experimental rations designated as T0, T1, T2 and T3 having 0g, 5g, 8g and 10g dried mushroom powder/kg of feed was fed to 120 broiler chicks (Cobb 500), randomly distributed into 8 replicates, so as to have 2 replicates per treatment containing 15 chicks in each. The experiment was carried out for 30 days. Average weight gain, feed consumption, feed efficiency, dressing yield and survivability were used as criteria of response to feeding mushroom powder. Organs weight including heart, liver and gizzard were also recorded. The mean body weight per broiler was 1292.24, 1501.66, 1445.19 and 1434.97g in 30 days for the treatment of groups T0, T1, T2, and T3 respectively (P<0.01). The average feed consumption per broiler was 2374.77, 2273.55, 2283.86 and 2276.3g (P<0.01) in 30 days for the groups of T0, T1, T2, and T3 respectively. The average feed efficiency (feed/kg body weight gain) was 1.84, 1.52, 1.58 and 1.59 (P<0.01) in 30 days for group T0, T1, T2, and T3 respectively. The mean dressing yield was 57.16%, 60.63%, 58.89% and 61.42% (P<0.01) for the groups of T0, T1, T2, and T3 respectively. The average weight of abdominal fat 2.69%, 1.55%, 1.74% and 1.65% (P<0.01) and heart was 8.5, 10.25, 8.5 and 7.6g (P<0.05). The average weight of liver was 43.1, 43.5, 46 and 43.5g (P>0.05) for the groups of T0, T1, T2, and T3 respectively. The mean gizzard weight was 35.25, 35, 34.5 and 35.75g (P>0.05) for the groups of T0, T1, T2, and T3 respectively. Survivability was 100%, for all the groups of T0, T1, T2, and T3 respectively. It may be concluded that the use of mushroom as feed additive at a level of 5g enhances the overall performance of broiler chicks. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 120-127